Contrast Coding: A Refinement of ANOVA in Behavioral Analysis. - Buckless, Frank A.; Ravenscroft, Sue Pickard (The Accounting Review, 1990)
Abstract Illustrates the increased statistical power of contrast coding over the conventional ANOVA on behavioral analysis, when multiple-level factors are involved or when certain types of interactive relationships among factors are hypothesized. Effect on Type I error rates; Limitations of ANOVA; Advantages of contrast coding; Empirical examples; Multi-level factors.